The lives and work of 12 further education based teacher educators in England - Fisher, Roy; Powell, David (University of Huddersfield Press, 2023)
This publication was inspired by the work of two Dutch teacher educators, Peter Lorist and Anja Swennen, who have done so much to promote understanding of the lives and work of teacher educators. What is distinctive about this booklet is that it exclusively focuses on one type of teacher educator working in one country: further education (FE) based teacher educators in England. Building on Noel's research into the 'secret life' of the FE based teacher educator, this booklet incorporates the directly told stories of 12 FE based teacher educators together with discussion and analysis which explores how they became teachers and then teacher educators. It considers the context of their work and explicates some common themes. Petrie asserted that 'writing about FE is...to draw a map' of it. As such, this booklet adds new detail to the still largely underdeveloped 'map' of FE initial teacher education. It is both an invitation to researchers to identify 'areas of the map for exploration' and a resource for teacher educators, particularly, those inducting and working with FE's new teacher educators.